Rekonstruksi Fiqh Digital Rumah Tangga: Analisis Maqāṣid al-Syarī‘ah Terhadap Cyber Domestic Violence dan Integrasi Hukum Positif di Indonesia - Asrori, Khozinatul; Al-Mubarok, Muhammad Zidan (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2025)
This article explores the phenomenon of cyber domestic violence as a contemporary form of violence emerging alongside technological advancements. Identifying a gap in Islamic legal scholarship on this issue, this research aims to analyze various forms of cyber violence, evaluate their impact on family integrity, and formulate an integrated protection framework that combines the perspectives of Islamic law and Indonesian positive law. Using a normative-qualitative legal research method with a maqāṣid al-syarīʿah approach, the findings indicate that practices such as digital surveillance, revenge porn, online intimidation, and digital isolation fundamentally contradict the principles of mu‘āsyarah bil ma‘rūf (good and proper conduct), the prohibition of tajassus (spying), and the universal maxim of lā ḍarar wa lā ḍirār (no harm, no reciprocating harm). These actions constitute a serious violation of the primary objectives of Sharia (maqāṣid), specifically in preserving life (ḥifẓ al-nafs) and honor (ḥifẓ al-‘ird). This research contributes originally by developing the concept of domestic digital fiqh and formulating an integration matrix that connects maqāṣid principles with the provisions of positive law (the Domestic Violence Law, the Electronic Information and Transactions Law, and the Law on Sexual Violence Crimes). This integration is expected to strengthen the moral and juridical legitimacy for prosecuting cyber violence, support the realization of a sakīnah (harmonious and peaceful) family in the digital era, and serve as a reference for policymakers and legal practitioners.